Pelatihan Dan Pendampingan Pengelolaan Keuangan Dan Pencatatan Pembukuan Administrasi Pelaporan Pajak Bagi Usaha Cacing Pupuk Organik Pada Kelompok Ternak Tunas Rinjani 2 Di Desa Selat Kecamatan Narmada - Endar Pituringsih; Lilik Handajani; Ayudia Sokarina (Jurnal Gema Ngabdi, 2023)
This counseling and training activity is about financial management and bookkeeping as a complete administrative tax reporting for the Tunas Rinjani livestock group in the Montong Daye Hamlet, Selat Village, Narmada District. It aims to provide understanding and knowledge about the Tunas Rinjani livestock group for financial management and bookkeeping as the completeness of tax reporting administration for businesses. compliance for small entrepreneurs in the Tunas Rinjani Livestock group in tax reporting. In addition, this training was conducted to provide knowledge to the Tunas Rinjani Cattle group about the importance of keeping bookkeeping records and the completeness of tax reporting so that they can be managed properly. In the end, this activity is expected to produce human resources who can keep records and get new ideas. This activity will be aimed at the Tunas Rinjani Training Cattle Group in the Montong Daye Hamlet, Selat Village, Narmada District. Implementation is carried out with the approach of providing relevant materials. Another hope of this activity can be a means to carry out community service, providing counseling and training in financial management and bookkeeping as tax reporting for livestock groups